Comparison of Microhardness of a Composite Core in Two Different Placement Techniques - An Invitro Study - Faramarz Zakavi; Somayeh Hosseini Tabatabaei; Fatemeh Bahramnejed; Soheila Sadeghian; Kaveh Khalaj; Mahdi Pourmahdi borujeni (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background and Objective: The purpose of this study was laboratory comparison of microhardness values in one kind of composite core at complete building tooth with incremental and Bulk placement techniques. Subjects and Methods: Ten cylindrical samples of clearfil photo core-light cure (Kuraray/Japan), (Translucent, Single Shade) composite were prepared up to 9mm in Insulin syringes. Half of them were built with incremental placement technique by 2 mm increments and the other half were built with bulk placement technique. Light curing was done with output irradiance of 650 mw/cm2 for 40 seconds. Samples were cut in longitudinal position and were mounted in Epoxy resin. Vicker's microhardness was measured from surface of every samples in the 1,2,3,4,5,6,7,8,9 mm depths. Statistical Analyses were done with two-way ANOVA (P<0.05).Results: The micro hardness values of equivalent depths in bulk placement technique were more than incremental placement. There were not significant diffenences among the hardness of 1 to 9 mm depths, in two placement techniques. Conclusion: In order to achieve the suitable curing depth in every composite with regard to its composition and color, we should follow the light curing standard conditions of that special composite.